KEBIJAKAN PAJAK PROGRESIF BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DALAM PERSPEKTIF KEADILAN PAJAK DAN POTENSI SENGKETA DI PERADILAN PAJAK ) - Hilma Syita El Asith; Muhammad Rustamaji; Jadmiko Anom Husodo (Sebelas Maret University, 2025)
Progressive BPHTB taxation constitutes a regional fiscal policy that functions not only as a revenue-raising (budgetary) instrument but also as a regulatory (regulerend) mechanism aimed at realizing social justice through a more equitable and fair distribution of land ownership. This study seeks to analyze the progressive taxation rules applicable to BPHTB from the perspective of tax justice and to identify potential disputes that may arise, as well as the role of the Tax Court in their resolution.The method employed in this study is a normative-juridical approach with a qualitative orientation. Its application relies on secondary data, encompassing primary legal materials in the form of statutory regulations and secondary legal materials in the form of books and scholarly journals. The discussion demonstrates that, philosophically, progressive taxation on BPHTB represents Aristotle’s concept of distributive justice, John Rawls’s difference principle, and modern theories of tax justice based on the ability-to-pay principle. All three emphasize proportional tax burdens according to individual capacity. The resulting tax revenues are subsequently utilized to enhance public welfare, particularly for groups considered less advantaged.Nevertheless, in practice, there is potential for disputes arising from disharmony between norms and their implementation, such as differences in the interpretation of the Tax Object Acquisition Value (NPOP), variations in Non-Taxable Acquisition Value (NOPTKP) policies among regions, and the perception that the application of progressive BPHTB taxation is disproportionate. The Tax Court plays a crucial role as a corrective mechanism to regional fiscal policies through objection, appeal, and judicial review procedures, ensuring that progressive BPHTB taxation remains within the legal framework and adheres to the principles of tax justice. Therefore, regulatory harmonization, transparency in determining NPOP, and the strengthening of the Tax Court are necessary to achieve a fair and sustainable regional taxation system.